(untitled) (Research, Society and Development, 2020)
Veterinary hospitals are significant generators of healthcare waste (HCW). The dangerousness attached to HCW represents an important factor for the matter of biosafety in health facilities. In this context, the objective of this work was to analyze the HCW management practices of an animal health care unit, as a basis for the elaboration and implementation of a Health Services Waste Management Plan (HSWMP). The research was descriptive exploratory, quantitative and qualitative, being developed in a veterinary hospital bounded to a higher education institution, located in the south of Rio Grande do Sul. Visits in loco and questionnaire application to the HCW generators were realized. The study showed that the management of this waste was not being carried out according to the law. Therefore, it is necessary to continue training people who involved in the management process, in addition to the implementation of the HSWMP in the unit.